综掘巷道超前支护装置支撑态动力学特性仿真研究 - 谢苗; 李政; 刘治翔; 刘一柱 (Ji xie qiang du, 2021)
In order to improve the dynamic stability of the advanced supporting device of the roadway,This paper studies the simulation of its support state dynamics.According to the structure and working principle of the supporting equipment,the Lagrangian method is used to establish the dynamic model of the multi-degree-of-freedom vibration system of the fully supported state of the self-moving support equipment.Establish a simulation model of the pre-support system under simulated dynamic disturbance,and apply a disturbance function to the single-group bracket and the whole machine model,Based on the ANSYS analysis software,the modal analysis of the single-group bracket and the whole machine in different states was carried out,and the first 6-order modal parameters of different states were obtained and compared.On the basis of modal analysis,the modal superposition method is used to analyze the harmonic response of single-group support and the whole machine,and its dynamic response characteristics are studied.Compari